Políticas públicas ambientais na expansão da agroindústria canavieira em Goiás: uma análise crítica do período 1999 a 2009 - Silva, José Humberto da (Universidade do Vale do Rio dos Sinos, 2010)
This research analyses the public policies for the environment adopted in the expansion of agribusiness in the Brazilian state of Goiás. It departs from concerns related to environmental impacts which could be generated by activities of this expansion. Studies have been carried out about public policies associated to the environment, to sustainable development as well as to Sugar Cane agribusiness in Brazil, particularly in Goiás. Looking for this aim, a pertinent literature revision was made looking at a better comprehension of concepts as well as at understanding how Sugar Cane agribusiness expansion process in Goiás occurred. The study started from the following question: which public policies for the environment have been adopted by the State of Goiás during the expansion of Sugar Cane agribusiness in the period from 1999 to 2009? It was aimed to study critically the adopted policies by means of the description and analysis of the main processes used in the elaboration of public policies for the environment for the Sugar Cane sector in Goiás. The existence of contributions brought by the public policies for the environment to the expansion of Sugar Cane agribusiness in Goiás was identified and the evolution of this sector in the State was shown. From the methodological view, the data have been produced by means of searching in specialized sites of agribusiness sector and interviews with actors involved in the Sugar Cane agribusiness process such as members of the public power, a searcher of environmental question, an ancient governor and representatives of the sector in the state. The results point towards the fact that the expansion occurred in the state has had its first steps in the years 1998 and 1999, when existed 11 Sugar Cane agribusiness unities. In 2005, when this expansion has been carried out there were 34 unities. The work points towards to that the expansion policies and the public policies for the environment start from the unfolding process of the environmental laws, within the federal ambit as well as within the state one, specially the law 6.938, which deals about the national policy to environment.
Keywords: Políticas públicas; Meio ambiente; Agroindústria canavieira; Public policy; Environment; Sugarcane industry; ACCNPQ::Ciências Sociais Aplicadas::Administração